2018
DOI: 10.1177/0192513x18765048
|View full text |Cite
|
Sign up to set email alerts
|

Narratives on the Autism Journey: “Doing Family” and Redefining the Caregiver Self

Abstract: Drawing on 50 in-depth semistructured interviews with primary caregivers of at least one child diagnosed with autism, this study demonstrates how the current social experience of caring for a child with an ambiguous and invisible disorder upsets the identities of primary caregivers and challenges their ability to perform the traditional Standard North American Family ideal and normative ways of “doing family.” Accordingly, I employ a narrative framework to (a) understand deeply how everyday autism care work af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…When validating the theoretical explanation, an interactive construction process began with the birth of the child that emphasized the temporality (as a succession of events) of the parental condition, since it constitutes a reference in the parents’ lives. Concomitantly, the specificity that surrounds this experience converts the experience into a unique, dynamic, complex process equipped with great challenges, [ 5 , 13 , 14 , 15 , 16 ] leading parents through the process to a new perception of the concept, translating it into a new way of thinking, feeling and acting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When validating the theoretical explanation, an interactive construction process began with the birth of the child that emphasized the temporality (as a succession of events) of the parental condition, since it constitutes a reference in the parents’ lives. Concomitantly, the specificity that surrounds this experience converts the experience into a unique, dynamic, complex process equipped with great challenges, [ 5 , 13 , 14 , 15 , 16 ] leading parents through the process to a new perception of the concept, translating it into a new way of thinking, feeling and acting.…”
Section: Discussionmentioning
confidence: 99%
“…The integration of the categories in the circle of the central category, and in the relationships between them, leads to an understanding of the chronology of events. The exercise of parenting develops over time through living with the child, where there is a succession of integrating events and where the process is characterized by continuous learning, changing and developing relationships, and by a profound renewal of the self [ 4 , 10 , 14 , 15 , 17 ]. This process of parenting proves to be a co-constructed process, inherent to the personal experiences of each parent and is involved in a very specific context that is the world of the spectrum of a child with ASD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…internal, internalized meanings and expectations associated with a role" (p. 289). As meaning is altered by the presence of disability, expectations associated with the role of being a parent change (Chiaraluce, 2018). Identity theory proposed that when a particular identity becomes salient in a situation, individuals act with the goal of aligning their perceived identity with identity standards.…”
Section: Theorymentioning
confidence: 99%
“…Prior literature suggested that individuals associated with a person with a stigmatized identity, such as parents of children with disabilities, also experience stigma from others, referred to as “courtesy” or “affiliate” stigma (Goffman, 1963; Gray, 2002; Green, Davis, Karshmer, Marsh, & Straight, 2005). Courtesy stigma can affect parents’ ability to appear “normal” to others (Gray, 2002), as well as parent’s ability to perform traditional normative family roles (Chiaraluce, 2018). As parents redefine their identities to deal with courtesy stigma and community norms, health behaviors may be altered.…”
Section: Introductionmentioning
confidence: 99%